Effects of Spray Gel Compared with The Methods of Using Interceed Seprafilm and Ringer Lactate for The Prevention of The Postoperative Adhesions - Kundak, Şazen; Güven, Davut; Süllü, Yurdanur; Üstün, Cazip; Erdoğan, Özgür; Koçak, İdris; Kılıço, İsmail (Gynecology Obstetrics & Reproductive Medicine, 2009)
OBJECTIVE: To compare the spray gel with the methods of using interceed, seprafilm or intraperitoneal lavage with ringer lactate, which are used to prevent the postoperative adhesions. STUDY DESIGN: The rats were randomly divided into 5 groups each including 10 rats. Laparatomy was performed via lower median incision. The first group (group 1) served as the control (nothing was given to prevent the adhesion). In group 2, 4 cc. Ringer lactate solution was instilled into the peritoneal cavity before abdominal closure. In group 3 Interceed (2 x 3 cm) was placed to the adhesion region. In the group 4 Seprafilm (2 x 3 cm) was used for to prevent adhesions. In the last group (group 5) spray gel was used 1 - 2 cc. to form 2 mm. thickness on the cauterized surface..Statistical evaluation was made using analysis of variance Kruskal - Wallis and Mann - Whitney U Tests and the results were accepted to be significant if the P<0.01. RESULTS: The postoperative average adhesion scores were found significantly decreased on the ringer lactate (p=0,00l), interceed (p=0,00l), seprafilm (p<0,001) and spray gel (p<0,001), groups compared to the control group.There were no statistical significant differences between the average adhesion scores of the groups which used spray gel: ringer lactate (p=0,473), interceed (P=0,888), and seprafilm (p= 1 ,000).(P>0,005). CONCLUSION: The effectiveness of the spray gel for the prevention of adhesion formation is found similar to the methods of ringer lactate, interceed and seprafilm.